IMPLEMENTASI PERATURAN DAERAH NOMOR 5 TAHUN 2003 TENTANG PENGENDALIAN KEBAKARAN HUTAN DAN LAHAN OLEH DINAS KEHUTANAN PROVINSI KALIMANTAN TENGAH - GIOVANY BAPTISTA AUGUSTA BRILIANTINE; ANYUALATHA HARIDISON (Journal Ilmu Sosial, Politik dan Pemerintahan, 2017)
One of disasters which often happens in dry season in Central Borneo is forest and land fires in areas which is owned by the people, plantation area, HPH area, HTI area and even protected area. Parts of the fire are because of the preparation that is done by the people by using the fire. From the condition, the prevention readiness and control of related parties in avoiding forest and land fires are needed in Central Borneo Province. The research aimed to: 1) to find out the implementation of Local Regulation number 5 in 2003. 2) to find out the obstacles of Forestry Department of Central Borneo Province in implementing The Local Regulation Number 5 in 2003. This research used descriptive qualitative data as the main data source. Data was collected by observation technique, interview and documentation. The technique to analyze the data used Miles and Huberman Model. Based on the result and discussion of the study, it could be drawn the conclusions as follows: 1) The implementation of Local Regulation Number 5 in 2003 has not been effective yet as operational to control forest and land fires because of the lack of infrastructure, the lack of human resources in the field and the lack of budget. 2) The indicator of communication was not run well between Department of Forestry and the people because there was miscommunication. 3) the resources in Department of forestry’s office has run well because there were information staff, authority and facility. 4) there was disposition including insentive and bureaucrat. 5) bureaucrat structures covered SOP and clear fragmentation. Suggestion 1) The related department which control the problem of forest and land fires is expected to work harder and more socialize or do the training practice to the people.